NUTRITION INFLUENCE ON THE CONDITION OF HUMAN JAW-TEETH SYSTEM: NUTRITION INFLUENCE ON THE CONDITION OF HUMAN JAW-TEETH SYSTEM - Adeishvili, Teimuraz; Aleksandrov, Aleksandar; Okrochelidze, Nino; Zhvitiashvili, Tengiz; Davarashvili, Khatuna (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
A nutrition process and its influence on the condition of human jaw-teeth system is considered to be one of the important aspects of research. In particular different kinds of diseases caused by life-giving, anti-nutrition and unknown genus substances are evaluated in the article. In this time the definite concentration of mercury, lead, cadmium, radon and other elements, penetrated in organism provoke pathological complications of dental systems.